Protein associated with SMAD1 (PAWS1/FAM83G) is a substrate for type I bone morphogenetic protein receptors and modulates bone morphogenetic protein signalling. Issue 2 (February 2014) - Vogt, Janis; Dingwell, Kevin S.; Herhaus, Lina; Gourlay, Robert; Macartney, Thomas; Campbell, David; Smith, James C.; Sapkota, Gopal P.
Abstract : Bone morphogenetic proteins (BMPs) control multiple cellular processes in embryos and adult tissues. BMPs signal through the activation of type I BMP receptor kinases, which then phosphorylate SMADs 1/5/8. In the canonical pathway, this triggers the association of these SMADs with SMAD4 and their translocation to the nucleus, where they regulate gene expression. BMPs can also signal independently of SMAD4, but this pathway is poorly understood. Here, we report the discovery and characterization of PAWS1/FAM83G as a novel SMAD1 interactor. PAWS1 forms a complex with SMAD1 in a SMAD4-independent manner, and BMP signalling induces the phosphorylation of PAWS1 through BMPR1A. The phosphorylation of PAWS1 in response to BMP is essential for activation of the SMAD4-independent BMP target genes NEDD9 and ASNS . Our findings identify PAWS1 as the first non-SMAD substrate for type I BMP receptor kinases and as a novel player in the BMP pathway. We also demonstrate that PAWS1 regulates the expression of several non-BMP target genes, suggesting roles for PAWS1 beyond the BMP pathway.